The ethnography of Tantra: textures and contexts of living Tantric traditions - Lorea, Carola Erika; Singh, Rohit (SUNY Press, 2023)
"Presents Tantra from an ethnographic vantage point, through a series of case studies grounded in diverse settings across contemporary Asia"--